Lectura extensiva en lengua extranjera usando la red social Facebook : una experiencia con estudiantes de grado once de la I.I. Cazucá - Soacha (2017)
The main purpose of this emporic study was to analyze how Extensive Reading (ER), influencies the reading comprehensive level in the english study as a foreign language (FL), in the students of eleventh grade from the Institución Educativa Cazucá, interacting with short texts through the social network Facebook used as an ICT tool. Therefore, under the reflection of my pedagogical practice, I formulate the following research question: How the implementaron of extensiva autonomous reading activities, proposed through the social network Facebook, has influence on the level of reading comprehension in english as a foreign language, in the students of eleventh grade from the Institución Educativa Cazuca? As for the results, I could understand that imparting knowledge in a traditional, structural and focused way to the grammar of school texts, did not allow the progress of young people in the work of reading comprehension and more difficult with the short time available. In the contrary, through a different strategy proposal, students were empowered to develop their own communicative competence from the reading comprehensivo of authentic texts in a foreign language. I believe that the main objective was achieved; It was possible to identify the incidente in the level of reading comprehensivo in LE of the activities based on Extensive Reading, using the social network Facebook as a tool in the service of education, through this strategy of reading that motivated, empowered autonomy and offered students the freedom to make decisions for the benefit of their own process. That is why the positive incidente of ER is identificó by gradual getting students to talk with the text presented in a foreign language, taking advantage of the particularity of the authentic texts that proved to have real meaning for students. The results of this research demostraste that the practice of extensive reading is highly beneficial for the development of a foreign language.